2021
DOI: 10.1109/access.2021.3077570
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability-Oriented Application of Value Stream Mapping: A Review and Classification

Abstract: Notwithstanding the research on refining lean tools for the sake of sustainable development is slowly progressing, sustainability-oriented application of value stream mapping has received undivided attention from practitioners and researchers. Going through the literature highlights that there is a lack of research in integrating and systematising the available knowledge on this lean tool, which is regarded as a visual process-based method to make sustainable progress over the time-based and green concepts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…To complement and support the societal aspects of sustainable-oriented lean practice research, Gholami et al (2019) developed a social value stream mapping methodology that can visualize and assess the societal sustainability performance in the context of LM. Lee et al (2021) integrated and systematized the state-of-the-art research studies of lean tool. They introduced value stream mapping from the triple bottom line point of view and proposed a sustainability indicator set.…”
Section: Resultsmentioning
confidence: 99%
“…To complement and support the societal aspects of sustainable-oriented lean practice research, Gholami et al (2019) developed a social value stream mapping methodology that can visualize and assess the societal sustainability performance in the context of LM. Lee et al (2021) integrated and systematized the state-of-the-art research studies of lean tool. They introduced value stream mapping from the triple bottom line point of view and proposed a sustainability indicator set.…”
Section: Resultsmentioning
confidence: 99%
“…Of Management and n n 2685-5992 (media (1) 2022 Lee, et al (2021), Garza-Reyes, et al (2018), and Rosenbaum, et al (2014. However, they do not mention how to involve all stakeholders in the application of GVSM.…”
Section: Conclusion and Future Implicationsmentioning
confidence: 99%
“…With the development of those research, some scholars suggested that the current research attention has mainly been given to the environmental issues, largely neglecting the societal aspects (Gholami et al, 2019). Therefore, the view of triple bottom line, circular economy, 3 R and 6 R continue to be mentioned by other scholars to achieve a more comprehensive VSM application (Galvão et al, 2020;Lee et al, 2021). To more accurately define and identify the waste associated with economic, environmental and social performance in business activities, Sus-VSM was carried out as a novel approach which integrates the concept of sustainability (Brown et al, 2014;Faulkner and Badurdeen, 2014).…”
Section: Abstract and Research Topic Analysismentioning
confidence: 99%
“…After that, the development of society and economy has aroused people’s attention to the concept of green and sustainable. VSM scholars and practitioners started to integrate relevant concepts, indexes and methods into conventional VSM (Lee et al , 2021), and proposed sustainable value stream mapping (Sus-VSM) (Faulkner and Badurdeen, 2014), energy VSM (Wen et al , 2021; Verma et al , 2021) and other approaches. At present, with the development of I4.0 technologies, VSM issues related to data and information processing have also received a lot of attention (Roh et al , 2019; Meudt et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation